Advances in civil engineering II : selected, peer reviewed papers from the 2nd International Conference on Civil Engineering and Transportation (ICCET 2012), October 27-28, 2012, Guilin, China - International Conference on Civil Engineering and Transportation (ICCET 2012) (2nd : 2012 : Guilin, China); Zhang, Xiangdong, editor; Li, Hongnan, editor; Feng, Xiating, editor; Chen, Zhihua, editor (Durnten-Zurich : Trans Tech Pub., 2013)
Includes bibliographical references and index